(untitled) (Педагогіка вищої та середньої школи, 2008)
This article considers the problem of formation of the professional competence of future specialists in the context of realization of the Competence-Based Approach in the higher professional school. It reveals the main points of view on its introduction and its results; it studies the structure and the main constituents of the professional competence of future specialists.